Preparation method of high-strength coal columnar activated carbon
By combining coal-based activated carbon with polymer zirconium chloride and organic polymers, and by sonication and grafting reaction of protocatechaldehyde, the problems of limited adsorption capacity and long contact time of coal-based activated carbon are solved, and efficient water treatment effect is achieved.
Patent Information
- Application Number
- CN202411442028.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-10-16
AI Technical Summary
The adsorption capacity of coal-based activated carbon is limited in water treatment and requires a long contact time to achieve the ideal purification effect.
Coal activated carbon and polymer zirconium chloride are used as inorganic adsorbents, and organic polymers are introduced for compounding. Through ultrasonic treatment and grafting reaction of protocatechaldehyde, a complex system with both inorganic and organic polymer adsorbents is formed.
It significantly improves the adsorption performance and mechanical strength of activated carbon, shortens the contact time, and improves the water treatment efficiency and water quality.
Smart Images

Figure BDA0005086590520000071 
Figure BDA0005086590520000081
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of activated carbon preparation, and relates to a method for preparing high-strength coal-based columnar activated carbon. Background Art
[0002] As an efficient adsorbent, activated carbon has been widely used in the field of drinking water treatment. Due to its excellent adsorption performance and purification effect, the application prospects of activated carbon in drinking water treatment are very broad, and its use is increasing year by year. my country has rich coal resources and huge coal reserves, which enables us to use coal resources to produce activated carbon on a large scale. By preparing activated carbon from coal, we can ensure a stable supply of output to meet market demand. Therefore, coal-based activated carbon has become a major type of activated carbon in the field of water treatment.
[0003] However, although coal-based activated carbon has certain advantages in water treatment, its adsorption capacity is relatively limited, and a longer contact time is required in practical applications to achieve the desired purification effect. In order to overcome these limitations, researchers and engineers have been working on the preparation and research of modified activated carbon. Through modification technology, the adsorption performance of activated carbon can be significantly improved, the contact time can be shortened, and thus the water treatment efficiency and water quality can be improved. Modification methods include physical modification, chemical modification, and biological modification, which can effectively increase the specific surface area of activated carbon, adjust the pore structure, and introduce new functional groups, so that it can play a greater role in water treatment. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing high-strength coal-based columnar activated carbon. The present invention uses coal-based activated carbon and polyzirconium chloride as inorganic adsorbents, and introduces organic polymers for compounding, so that the compound system has the characteristics of both inorganic and organic polymer adsorbents, and has both charge neutralization effect and strong macromolecular trapping effect.
[0005] The purpose of the present invention can be achieved by the following technical solutions:
[0006] A method for preparing high-strength coal-based columnar activated carbon comprises the following steps:
[0007] Step S1: placing activated carbon, polyzirconium chloride and deionized water in a stirrer, stirring and mixing, allowing the mixture to settle and stand, filtering, washing with deionized water, and drying in an oven to obtain prefabricated activated carbon;
[0008] Step S2: soaking the prefabricated activated carbon in the mixed solution, mixing well, and then performing ultrasonic treatment to obtain a prefabricated solution;
[0009] Step S3: the preformed liquid is placed in an ethanol solution and mixed evenly, protocatechuic aldehyde is added and stirred at a constant temperature, then ultrasonic treatment is performed, rotary evaporation treatment is performed, ethanol is used for washing, and the solution is placed in an oven for drying to obtain the product.
[0010] As a preferred technical solution of the present invention, the activated carbon is coal-based activated carbon, which is made from Taixi washed clean coal. After being crushed to 80 μm, an appropriate amount of coal tar (50%) is added and kneaded into columnar particles in a kneading equipment. The activated carbon is obtained after carbonization at a temperature of 600°C and carbonization for 1 hour.
[0011] As a preferred technical solution of the present invention, in step S1, the stirring and mixing is stirring at a speed of 600-800 r / min for 10-12 hours; and the drying is drying at a temperature of 60-70° C. for 3-4 hours.
[0012] As a preferred technical solution of the present invention, in step S1, the mass ratio of the activated carbon, polyzirconium chloride and deionized water is 4-5:1.0-1.3:40-50.
[0013] As a preferred technical solution of the present invention, in step S2, the ultrasonic treatment is 800-1000W frequency ultrasound for 10-15min.
[0014] As a preferred technical solution of the present invention, in step S2, the mixed solution is formed by mixing chitosan, fulvic acid and deionized water in a mass ratio of 3.6-4.0:1.2-1.4:180-200.
[0015] As a preferred technical solution of the present invention, in step S2, the mass ratio of the prefabricated activated carbon to the mixed solution is 18-20:100-110.
[0016] As a preferred technical solution of the present invention, in step S3, the constant temperature stirring is stirring at 25-28°C for 14-16h; the number of ethanol washing is three times; and the drying is drying at 50-60°C to constant weight.
[0017] As a preferred technical solution of the present invention, in step S3, the ultrasonic treatment is performed at a frequency of 600-700W for 10-12min.
[0018] As a preferred technical solution of the present invention, in step S3, the mass ratio of the prefabricated liquid, the ethanol solution and protocatechuic aldehyde is 13-16:50-60:1.6-1.8; the concentration of the ethanol solution is 90wt%.
[0019] Beneficial effects of the present invention:
[0020] The present invention uses coal-based activated carbon and polyzirconium chloride as inorganic adsorbents, and introduces organic polymers for compounding, so that the compounded system has the characteristics of both inorganic and organic polymer adsorbents, has both charge neutralization function and strong macromolecular netting function.
[0021] Specifically, the present invention promotes the freeing of chitosan amino groups through the weak acid property of fulvic acid, low temperature can slow down the reaction between amino groups and aldehyde groups, which is beneficial to the formation of microporous and mesoporous structures, and ultrasonic treatment can reduce the interaction between fulvic acid and chitosan, so that more amino groups are exposed, and the grafting amount of protocatechuic aldehyde is promoted; the present invention uses coal-based activated carbon and polyzirconium chloride as inorganic adsorbents, and polyzirconium chloride enhances the strength and water resistance stability of activated carbon. By compounding fulvic acid and chitosan to form a macromolecular organic network, the dihydroxyl group of protocatechuic aldehyde is used to further promote stability, and compounding with the inorganic adsorbent makes the compound system have the characteristics of both inorganic and organic polymer adsorbents, and has both charge neutralization effect and strong macromolecular net capturing effect. DETAILED DESCRIPTION
[0022] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0023] Example 1
[0024] A method for preparing high-strength coal-based columnar activated carbon comprises the following steps:
[0025] Step S1: placing activated carbon, polyzirconium chloride and deionized water in a stirrer, stirring and mixing, allowing the mixture to settle and stand, filtering, washing with deionized water, and drying in an oven to obtain prefabricated activated carbon;
[0026] Step S2: soaking the prefabricated activated carbon in the mixed solution, mixing well, and then performing ultrasonic treatment to obtain a prefabricated solution;
[0027] Step S3: the preformed liquid is placed in an ethanol solution and mixed evenly, protocatechuic aldehyde is added and stirred at a constant temperature, then ultrasonic treatment is performed, rotary evaporation treatment is performed, ethanol is used for washing, and the solution is placed in an oven for drying to obtain the product.
[0028] In step S1, the stirring and mixing is performed at a rotation speed of 600 r / min for 10 hours; the drying is performed at a temperature of 60° C. for 3 hours; and the mass ratio of the activated carbon, polyzirconium chloride and deionized water is 4:1.0:40.
[0029] In step S2, the ultrasonic treatment is 800W frequency ultrasound for 10 minutes; the mixed solution is formed by mixing chitosan, fulvic acid and deionized water in a mass ratio of 3.6:1.2:180; the mass ratio of the prefabricated activated carbon to the mixed solution is 18:100.
[0030] In step S3, the constant temperature stirring is stirring at 25°C for 14 hours; the ultrasonic treatment is ultrasonication at a frequency of 600W for 10 minutes; the ethanol washing is performed three times; the drying is dried at 50°C to constant weight; the mass ratio of the prefabricated liquid, ethanol solution and protocatechuic aldehyde is 13:50:1.6; and the concentration of the ethanol solution is 90wt%.
[0031] Example 2
[0032] A method for preparing high-strength coal-based columnar activated carbon comprises the following steps:
[0033] Step S1: placing activated carbon, polyzirconium chloride and deionized water in a stirrer, stirring and mixing, allowing the mixture to settle and stand, filtering, washing with deionized water, and drying in an oven to obtain prefabricated activated carbon;
[0034] Step S2: soaking the prefabricated activated carbon in the mixed solution, mixing well, and then performing ultrasonic treatment to obtain a prefabricated solution;
[0035] Step S3: the preformed liquid is placed in an ethanol solution and mixed evenly, protocatechuic aldehyde is added and stirred at a constant temperature, then ultrasonic treatment is performed, rotary evaporation treatment is performed, ethanol is used for washing, and the solution is placed in an oven for drying to obtain the product.
[0036] In step S1, the stirring and mixing is performed at a rotation speed of 700 r / min for 11 hours; the drying is performed at a temperature of 65° C. for 3.5 hours; and the mass ratio of the activated carbon, polyzirconium chloride and deionized water is 4.5:1.2:45.
[0037] In step S2, the ultrasonic treatment is 900W frequency ultrasound for 12 minutes; the mixed solution is formed by mixing chitosan, fulvic acid and deionized water in a mass ratio of 3.8:1.3:190; the mass ratio of the prefabricated activated carbon to the mixed solution is 19:105.
[0038] In step S3, the constant temperature stirring is stirring at 26°C for 15 hours; the ultrasonic treatment is ultrasonic treatment at a frequency of 650W for 11 minutes; the ethanol washing is performed three times; the drying is performed at 55°C to constant weight; the mass ratio of the prefabricated liquid, ethanol solution and protocatechuic aldehyde is 14:55:1.7; and the concentration of the ethanol solution is 90wt%.
[0039] Example 3
[0040] A method for preparing high-strength coal-based columnar activated carbon comprises the following steps:
[0041] Step S1: placing activated carbon, polyzirconium chloride and deionized water in a stirrer, stirring and mixing, allowing the mixture to settle and stand, filtering, washing with deionized water, and drying in an oven to obtain prefabricated activated carbon;
[0042] Step S2: soaking the prefabricated activated carbon in the mixed solution, mixing well, and then performing ultrasonic treatment to obtain a prefabricated solution;
[0043] Step S3: the preformed liquid is placed in an ethanol solution and mixed evenly, protocatechuic aldehyde is added and stirred at a constant temperature, then ultrasonic treatment is performed, rotary evaporation treatment is performed, ethanol is used for washing, and the solution is placed in an oven for drying to obtain the product.
[0044] In step S1, the stirring and mixing is performed at a rotation speed of 800 r / min for 12 hours; the drying is performed at a temperature of 70° C. for 4 hours; and the mass ratio of the activated carbon, polyzirconium chloride and deionized water is 5:1.3:50.
[0045] In step S2, the ultrasonic treatment is 1000W frequency ultrasound for 15 minutes; the mixed solution is formed by mixing chitosan, fulvic acid and deionized water in a mass ratio of 4.0:1.4:200; the mass ratio of the prefabricated activated carbon to the mixed solution is 20:110.
[0046] In step S3, the constant temperature stirring is stirring at 28°C for 16 hours; the ultrasonic treatment is ultrasonication at a frequency of 700W for 12 minutes; the ethanol washing is performed three times; the drying is dried at 60°C to constant weight; the mass ratio of the prefabricated liquid, ethanol solution and protocatechuic aldehyde is 16:60:1.8; and the concentration of the ethanol solution is 90wt%.
[0047] Comparative Example 1
[0048] Compared with Example 3, the difference in Comparative Example 1 is that activated carbon replaces polyzirconium chloride, and the other components, preparation steps and parameters are the same.
[0049] Comparative Example 2
[0050] Compared with Example 3, the difference in Comparative Example 2 is that fulvic acid replaces chitosan, and the other components, preparation steps and parameters are the same.
[0051] Comparative Example 3
[0052] Compared with Example 3, the difference in Comparative Example 3 is that chitosan replaces fulvic acid, and the other components, preparation steps and parameters are the same.
[0053] Comparative Example 4
[0054] Compared with Example 3, Comparative Example 4 is different in that protocatechuic aldehyde is not used, and the other components, preparation steps and parameters are the same.
[0055] Comparative Example 5
[0056] Compared with Example 3, the difference of Comparative Example 5 is that step S3;
[0057] In step S3, the constant temperature stirring is stirring at 40°C for 16 hours; the ultrasonic treatment is ultrasonic treatment at 700W frequency for 12 minutes; the number of ethanol washing is three times; the drying is drying at 60°C to constant weight; the mass ratio of the prefabricated liquid, ethanol solution and protocatechuic aldehyde is 16:60:1.8; the concentration of the ethanol solution is 90wt%;
[0058] The remaining components, preparation steps and parameters were the same.
[0059] Comparative Example 6
[0060] Compared with Example 3, the difference in Comparative Example 6 is that in step S3, ultrasonic treatment is not performed in step S3, and the other components, preparation steps and parameters are the same.
[0061] The activated carbons prepared in Examples 1-3 and Comparative Examples 1-6 were subjected to the following performance tests.
[0062] Stability test: After the activated carbon is placed in water for 60 days, the strength is tested according to the activated carbon ball-disc method of GB / T 20451-2006;
[0063] Adsorption test: Static adsorption experiments were conducted on methanol, benzene and n-hexane. The static adsorption results are shown in Table 2;
[0064] Table 1
[0065] Strength (MPa) Example 1 3.3 Example 2 3.5 Example 3 3.6 Comparative Example 1 1.8 Comparative Example 2 2.0 Comparative Example 3 2.4 Comparative Example 4 2.5 Comparative Example 5 2.4 Comparative Example 6 2.6
[0066] From the test results in Table 1, it can be seen that compared with Comparative Examples 1-6, the mechanical strength of the activated carbon prepared in Examples 1-3 of the present invention is significantly better than that of the activated carbon prepared in Comparative Examples 1-6.
[0067] Table 2
[0068]
[0069]
[0070] From the test results in Table 2, it can be seen that compared with Comparative Examples 1-6, the adsorption capacity of the activated carbon prepared in Examples 1-3 of the present invention in a liquid environment is significantly better than that of the activated carbon prepared in Comparative Examples 1-6.
[0071] The invention promotes the freeing of chitosan amino groups by the weak acid property of fulvic acid, the low temperature can slow down the reaction between the amino group and the aldehyde group, which is beneficial to the formation of micropores and mesoporous structures, and the ultrasonic treatment can reduce the interaction between fulvic acid and chitosan, so that more amino groups are exposed, and the grafting amount of protocatechuic aldehyde is promoted; the invention uses coal-based activated carbon and polyzirconium chloride as inorganic adsorbents, the polyzirconium chloride enhances the strength and water resistance stability of the activated carbon, and forms a macromolecular organic network by compounding fulvic acid and chitosan, further promoting the stability by the dihydroxyl group of protocatechuic aldehyde, and compounding with the inorganic adsorbent, so that the compound system has the characteristics of both inorganic and organic polymer adsorbents, and has both the function of neutralizing charges and the strong net-catching function of macromolecules.
[0072] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for preparing high-strength coal-based columnar activated carbon comprises the following steps: Step S1: placing activated carbon, polyzirconium chloride and deionized water in a stirrer, stirring and mixing, allowing the mixture to settle and stand, filtering, washing with deionized water, and drying in an oven to obtain prefabricated activated carbon; Step S2: soaking the prefabricated activated carbon in the mixed solution, mixing well, and then performing ultrasonic treatment to obtain a prefabricated solution; Step S3: the preformed liquid is placed in an ethanol solution and mixed evenly, protocatechuic aldehyde is added and stirred at a constant temperature, then ultrasonic treatment is performed, rotary evaporation treatment is performed, ethanol is used for washing, and the solution is placed in an oven for drying to obtain the product.
2. The method for preparing high-strength coal-based columnar activated carbon according to claim 1, characterized in that: In step S1, the stirring and mixing is performed at a rotation speed of 600-800 r / min for 10-12 hours; and the drying is performed at a temperature of 60-70° C. for 3-4 hours.
3. The method for preparing high-strength coal-based columnar activated carbon according to claim 1, characterized in that: In step S1, the mass ratio of the activated carbon, polyzirconium chloride and deionized water is 4-5:1.0-1.3:40-50.
4. The method for preparing high-strength coal-based columnar activated carbon according to claim 1, characterized in that: In step S2, the ultrasonic treatment is 800-1000W frequency ultrasound for 10-15 min.
5. The method for preparing high-strength coal-based columnar activated carbon according to claim 1, characterized in that: In step S2, the mixed solution is prepared by mixing chitosan, fulvic acid and deionized water in a mass ratio of 3.6-4.0:1.2-1.4:180-200.
6. The method for preparing high-strength coal-based columnar activated carbon according to claim 1, characterized in that: In step S2, the mass ratio of the prefabricated activated carbon to the mixed solution is 18-20:100-110.
7. The method for preparing high-strength coal-based columnar activated carbon according to claim 1, characterized in that: In step S3, the constant temperature stirring is stirring at 25-28°C for 14-16h; the ethanol washing is performed three times; and the drying is drying at 50-60°C to constant weight.
8. The method for preparing high-strength coal-based columnar activated carbon according to claim 1, characterized in that: In step S3, the ultrasonic treatment is performed at a frequency of 600-700W for 10-12 minutes.
9. The method for preparing high-strength coal-based columnar activated carbon according to claim 1, characterized in that: In step S3, the mass ratio of the prefabricated liquid, the ethanol solution and protocatechuic aldehyde is 13-16:50-60:1.6-1.8; and the concentration of the ethanol solution is 90wt%.
Citation Information
Patent Citations
Adsorption treatment method for heavy metal ion-containing wastewater
CN107337249A
Preparation method of compound adsorbent for dyestuff wastewater
CN107661750A
Fulvic acid type three-dimensional network composite material, and preparation method and application thereof
CN109912755A
Preparation method of non-woven fabric with adsorption function
CN112569906A
Preparation method of high-strength antibacterial high polymer material and application of high-strength antibacterial high polymer material in water emulsion bottle
CN115304898A